¿Guerra o torneo?: la Batalla de Olmedo, modelo de enfrentamiento caballeresco - Castillo Cáceres, Fernando (En la España Medieval, 2009)
Military, political and chivalric characteristics of the battle of Olmedo (1445), which pitted John II of Castile and don Álvaro de Luna against part of the nobility led by the princes of Aragon. Analysis of the forces present, attitudes regarding combat and the convergence of the characteristics and rules of military confrontations with those of the courtly tournament, given the common social origins of the combatants on both sides.
Keywords: Castile 15th century; John II of Castile; Álvaro de Luna; Aragonese princes; War; Cavalry; Tournament; Battle of Olmedo (1445)